Odpowiedzi

Najlepsza Odpowiedź!
2010-02-20T11:01:54+01:00
A)3(x-4)-4(2x-7)=2(x+5)
3x-12-8x+28 = 2x +10
3x-8x-2x = 10+12-28
-7x = -6 / : (-7)
x = ⁶/₇

b)2(2x-3)+3(4-x)=-(x+1)
4x-6+12-3x = -x-1
4x-3x+x = -1+6-12
2x = -7 / :2
x = - ⁷/₂ = - 3½

c) 2(x-3)-4(3+x)=-3(x+2)+2(2x-1)
2x-6-12-4x = -3x-6+4x-2
2x-4x+3x-4x = -6-2+6+12
-3x = 10 / :(-3)
x = - ¹⁰/₃ = - 3⅓

d)6(x+1)+3(2-x)=2(2x-1)-(4-x)
6x+6 + 6 -3x = 4x - 2 -4 +x
6x-3x-4x-x = -2-4-6-6
-2x = -18 / : (-2)
x = 9
2010-02-20T11:03:58+01:00
A) 3x-12-8x+28=2x+10
3x-8x-2x=10+12-28
-7x=-6/:(-7)
x=6/7

b)4x-6+12-3x=-x-1
4x-3x+x=-1+6-12
2x=-7/:2
x=-3,5

c)2x-6-12-4x=-3x-6+4x-2
2x-4x+3x-4x=-6-2+6+12
-3x=10/:(-3)
x=10/3
x=3 ⅓

d)6x+6+6-3x=4x-2-4+x
6x-3x-4x-x=-2-4-6-6
-2x=-18/:(-2)
x=9

Mam nadzieje, ze pomoglam ;)
2010-02-20T11:08:36+01:00
A)
3(x-4)-4(2x-7)=2(x+5)
3x-12-8x+28=2x+10
3x-8x-2x=10+12-28
-7x=-6
x=6/7

b)
2(2x-3)+3(4-x)=-(x+1)
4x-6+12-3x=-x-1
4x-3x+x= -1+6-12
2x= -7
x= -7/2

c)
2(x-3)-4(3+x)=-3(x+2)+2(2x-1)
2x-6-12-4x= -3x-6+4x-2
2x-4x+3x-4x=-6-2+6+12
-3x=+10
x= -10/3

d)
6(x+1)+3(2-x)=2(2x-1)-(4-x)
6x+6+6-3x=4x-2-4+x
6x-3x-4x-x= -2-6-6-4
-2x= -18
x= 9